Urban Regeneration and the “Portmán. Full Stop and Continue” Brand: From Ecological Disaster to Sustainable Tourism Destination - Hernández Gómez, Onésimo Samuel (Street Art & Urban Creativity, 2025)
The article analyzes the process of urban regeneration and the resignification of the environmental disaster of Portmán Bay, focusing on the local Tourism Sustainability Plan. Urban planning and branding interventions are highlighted as part of a communicative strategy that seeks to transform the image of Portmán from a space marked by the mining impact to a sustainable tourist destination. We employed a mixed qualitative methodology that includes a case study, a semiotic analysis and an in-depth interview. The results demonstrate how the resignification of the past becomes an opportunity for responsible tourism development. The “Portmán” brand is presented as a symbol of resilience, supported by a coherent visual discourse and a narrative of continuity that connects past and future. Urban regeneration not only rehabilitates spaces but also articulates a narrative that reinforces the identity of the destination and its tourist projection.